Carica papaya induces in vitro thrombopoietic cytokines secretion by mesenchymal stem cells and haematopoietic cells - Aziz, Jazli; Abu Kassim , Noor Lide; Abu Kasim, Noor Hayaty; Haque, Nazmul; Rahman, Mohammad Tariqur (BioMed Central, 2015)
Background Use of Carica papaya leaf extracts, reported to improve thrombocyte counts in dengue patients, demands further analysis on the underlying mechanism of its thrombopoietic cytokines induction